ANALISIS PENEGAKAN HUKUM TERHADAP PERJUDIAN ONLINE BERDASARKAN UNDANG-UNDANG NO 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Agung, Dirga; Pratiwi, Andi Dewi; Aprilliana A.T, Lidwina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research was conducted with the aim of describing law enforcement against online gambling, regarding the laws governing and sanctions received. The research method used is the Normative Legal research method. where secondary data is used, namely a literature review and statutory regulations governing online gambling. In analyzing legal norms using a normative juridical approach among others : theories of law enforcement against gambling, factors that encourage online gambling, the impact caused and its responsibility for violations of legal norms that can be disruptive and detrimental to the perpetrators and even the majority of Indonesian society, including financial problems, disrupting productivity in work and business, Hinders career advancement and damages mental and emotional health. The steps taken by the government are the formation of an integrated cross-ministerial task force to eradicate online gambling, education and socialization, blocking websites that can access online gambling, prevention and rehabilitation for those who have become victims of online gambling.